THE ANALYSIS OF HUMAN CAPITAL BUILDING AND FINANCIAL ASSISTANCE ON SMALL MEDIUM ENTERPRISES DEVELOPMENT IN MANADO AND TOMOHON - Tumiwa, Johan; Paruntu, Carolus P. (Journal of Asean Studies on Maritime Issues, 2017)
In ASEAN, Indonesia as one of the developing countries that is continuously preparing themselves in order to compete with other countries in the case of ASEAN single market. Small Medium Enterprise is the best solution to facing the ASEAN Single Market and also to face unemployment as a one of Indonesia’s problem. Small and medium enterprises play an important role for Indonesia economy development and also generating employment. The development of small and medium enterprises in urban areas is needed. Beside the vital role of SMEs to contributing significantly to economic growth and job creation SMEs are facing more challenges to operations and to grow from factors both inside and outside: the lack of access to external financing, and need human capital building. The objective of this research is to analyze human capital building and finance assistance to development of small and medium enterprise in Manado and Tomohon. The research type is quantitative research that associative with multiple linear regression analysis technique. There are 100 participant of SMEs are participated in this research. The result of this research shows that there is significant simultaneous and partial influence of Human Capital Building and Financial Assistance on small medium enterprises development in Manado and Tomohon. Regarding on the result to enhance the development of SMEs in Manado and Tomohon these proponents should be considered intensively.Keywords: Financial Assistance, Human Capital Bilding, Micro and Small Enterprises